Evidence of communication, influence and behavioural norms in interprofessional teams: a realist synthesis. Issue 2 (March 2015) - Hewitt, Gillian; Sims, Sarah; Harris, Ruth
Abstract This article is the third in a series reporting the process and findings of a realist synthesis of interprofessional teamwork in health and social care. The synthesis articulated and tested four "mechanisms" (processes) of teamwork related to communication and found variable evidence to support them. Evidence was strongest for "efficient, open and equitable communication" and "tactical communication", but lacking for the shared responsibility element of the "shared responsibility and influence" mechanism. Little evidence was found to support or oppose the mechanism, "team behavioural norms", so its status as a mechanism of interprofessional teamwork is unclear. A striking finding for all the mechanisms was the dearth of information on how they affected patient clinical outcomes and experiences.